Negative correlation between Placental Growth Factor and Endocan-1 in women with preeclampsia - Ribiero Hentchke, Marta; Mistry, Hiten D.; Pinheiro da Costa, Bartira Ercilia; Poli-de-Figueiredo, Carlos Eduardo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Objective: To analyse Endocan-1, a biomarker of vascular endothelial related pathologies, and Placental growth factor (PlGF), an angiogenic factor and a placental dysfunction marker in patients with pre-eclampsia (PE). Methods: Case-control study conducted at São Lucas Hospital. Endocan-1 and PlGF levels were quantified in maternal plasma using MagPlexTH-C microspheres system and analysed by ANCOVA adjusted by BMI, gestational age and maternal age. To estimate the difference between groups, mean ratio (MR) and 95% confidence interval (CI) were calculated. Pearson correlation test was used to establish any association between Endocan-1 and PlGF levels. The null hypothesis was rejected when p<0.05. Results: The group of patients was composed by normotensive (n=67) and patients with PE (n=50). A negative correlation between Endocan-1 and PlGF was noted in the entire group (r= -0,605; p< 0.001); as well as in the PE group (r= -0,545; p< 0.001). Conclusion: Endocan-1 levels are increased in patients with PE and inversely correlated with PlGF levels. We suggest that it is important to analyze angiogenic and pro-inflammatory molecules concomitantly in women with PE to better understand the disease pathophysiology. Both molecules are strong competitors as a PE biomarkers and future work will examine any mechanisms connecting these factors in PE.